Penerapan Metode Pembelajaran Reward and Punishmant dalam Melatih Child Psychology - Faizin Faizin; Fathor Rozi; Ratna Sari (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to determine how the learning outcomes of the reward and punishment method, whether the provision of reward and punishment can improve the discipline and motivation of students and what forms of reward and punishment are given. This research uses a qualitative case study approach. This research is located in MI Ihyauddiniyah, Kecik Village, Besuk District, Probolinggo Regency, East Java. Sources of data obtained through observation and interviews. The resource persons in this study amounted to 6 people, namely the head of the Madrasa, 1 teacher, homeroom teacher for class V and 3 students. The application of the reward and punishment learning method at MI Ihyauddiniyah Kecik Probolinggo has a positive impact on students in terms of discipline and learning motivation. The forms of rewards applied at MI Ihyauddiniyah include; sincere compliment, memorial award, useful gift. The punishments applied at MI Ihyauddiniyah include: cue penalty, spoken punishment, corporal punishment.